2001
DOI: 10.1016/s0149-7189(01)00014-3
|View full text |Cite
|
Sign up to set email alerts
|

The correlates and predictive validity of HIV risk groups among drug users in a community-based sample: methodological findings from a multi-site cluster analysis

Abstract: Outreach and intervention with out-of-treatment drug users in their natural communities has been a major part of our national HIV-prevention strategy for over a decade. Intervention design and evaluation is complicated because this population has heterogeneous patterns of HIV risk behaviors. The objectives of this paper are to: (a) empirically identify the major HIV risk groups; (b) examine how these risk groups are related to demographics, interactions with others, risk behaviors, and community (site); and (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Wechsberg et al showed that identifying differential intervention outcomes for different subgroups of women may help inform future efforts to tailor and target behavioral interventions. Although responses to risk reduction interventions vary, the patterns of change over time are not known (Dennis, Wechsberg, McDermeit, Campbell, & Rasch, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Wechsberg et al showed that identifying differential intervention outcomes for different subgroups of women may help inform future efforts to tailor and target behavioral interventions. Although responses to risk reduction interventions vary, the patterns of change over time are not known (Dennis, Wechsberg, McDermeit, Campbell, & Rasch, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual behavior that increases the risk of HIV infection or transmission may also be associated with poly-substance use (Dennis, Wechsberg, McDermeit, Campbell, & Rasch, 2001;Lang & Belenko, 2001). The current samples were recruited for drug treatment research studies, and therefore study participants had a history of drug use.…”
Section: Classification Variablesmentioning
confidence: 99%
“…We employed a cluster analysis of observed sex-and drug-risk behaviors, established within the national multisite study [5,44], to classify each individual in the target population into one of eight risk groups. Each risk group has a distinctive pattern of social behavior in terms of drug use (category, method, and frequency) and sexual behavior (sexual acts, frequency, barter for drugs/money, baseline protection).…”
Section: Target Populationmentioning
confidence: 99%